Daya Tarik Wisata Rohani Gua Kerep Ambarawa - T. Prasetyo Hadi Atmoko (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2016)
Central Jawa Province obviously one of the tourist destinations in Indonesia either nature or historical and cultural attractions. The existence of Mary Cave Kerep Ambarawa also contributes to tourism in Central Jawa as the attraction of spiritual tourism. The objectives of this research are to acknowledge how to access the location of Mary Cave Kerep Ambarawa as well as to recognize how are the facilities that support Mary Cave Kerep Ambarawa. The methods of research being used are observation, interview and book study. Mary Cave Kerep Ambarawa resides in Jl. Tentara Pelajar, Dusun Kerep, Panjang Sub-district, Ambarawa District, Semarang Regency, Central Jawa Province. Geographically Mary Cave Kerep Ambarawa is located on the south slope hill of Ungaran mountain. The attraction of Mary Cave Kerep Ambarawa appeals from its Mary Cave views. It is the highest Mother Mary statue in the world and its inscriptions. Mary Cave Kerep Ambarawa is shaped in an artificial cave with a stacked stone bonded with cement, sand and lime. The cave overlooks to the east and is shaded by tall trees and lush. From one of the caves, there is a statue of Mother Mary Lourdes style without a crown. Viewed from the access, to object of religious tourism in Mary Cave Keep with an area around 5 hectares or more is not stiff. When leaving the city of Semarang the visitor can be able to grab a Yogyakarta line bus. Vice versa, when leaving from Yogyakarta select bus to Semarang, down to Ambarawa terminal. Similarly, when using personal vehicle travel to Semarang- Yogyakarta route, arrive at Ambarawa terminal bus, there is a signpost for the entrance to the tourist attraction, which is the entrance to the west and down to the ramp about 1KM. The facilities are provided in Mary Cave Keep Ambarawa specifically: hall, transit building, and prayer room, parking lot, shops object spiritual, church, food stalls around the area of the Cave, and accommodation, such as hotels and homestay.